Learning English Proper Names: A Case Study on the Challenge Faced by Russian-Speaking English Language Learners - Korneeva Olga Stepanovna (Development in Language Studies, 2025)
Anthroponyms, as a rule, are not given enough attention in the process of teaching English. As a result of the author’s practical experience in teaching English to Russian-speaking students, a number of learning difficulties faced by students have been identified. The research aims to determine which linguistic aspect deserves special attention in the mastering of anthroponyms. To achieve this, quantitative testing was conducted using a multiple-choice test on Google Forms to collect data and median measures to analyse the results. The results revealed the need to teach extralinguistic properties (name gendering and diminutives), while grammatical and phonetic properties of proper names did not prove to be very problematic, which is related to the presence of phonetics and grammar as separate subjects on the syllabus.